Redefined Innovation Ecosystem Promoting the Innovation Activities of the Hungarian Enterprises - Zoltán Birkner; Zsófia Hartyányi; Nora Rodek (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Recognizing the global technological, societal and economical megatrends and challenges, national innovation systems have to be restructured to be more open and flexible. The European Union, its member states, including Hungary have to react as the competitiveness on regional and national level is deteriorating constantly compared to other leading regions in the world. New goals, tools and methods have to be implemented on national level as well. The Hungarian government targets to reshape the national innovation ecosystem with the aim to be more reflexive, sustainable and competitive. The actors (including universities, research centres and enterprises) have to redefine their roles and cooperate on a mutually beneficial basis. A redefined innovation ecosystem is planned to develop according to the Quintuple Helix which is not only a theoretical model but a functioning system. This study presents the steps the Hungarian government did toward an open innovation regulatory system, its RDI strategy as well as the results of our latest research conducted among Hungarian enterprises focusing on their innovation activities. The results show in what aspects the new strategy can support the needs of the businesses.
Keywords: O35; 330; innovation; innovation ecosystem; RDI strategy